Investment in Photovoltaics and Job Creation: Evidence from a Billion Dollar Program - Matthias Wilhelm; Lukas Buchheim; Martin Watzinger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the labor market effects of a exteuro60 billion investment program in photovoltaics in Germany between 2003 and 2012. According to our estimates, the program created one job lasting one year for every exteuro120,000 in investment. Gains were concentrated in the construction sector, with spillovers to local services. The effects are stronger in weaker economic times. To address endogeneity concerns, we exploit the fact that local investment was pre-determined by the amount of available rooftops and solar radiation in a region to construct an instrumental variable estimator.
Keywords: E24; E62; R23; 330